1977
DOI: 10.1029/jb082i011p01667
|View full text |Cite
|
Sign up to set email alerts
|

Geodetic measurements of deformation associated with the Oroville, California, earthquake

Abstract: Comparison of preearthquake vertical geodetic surveys with postearthquake surveys in the region affected by the magnitude 5.7 Oroville earthquake of August 1, 1975, indicates appreciable elevation changes. The data are consistent with 0.36 m of normal slip on a 12×10 km2 rectangular fault dipping 60° to the west. Comparison of level surveys run 1 and 6 months after the earthquake suggests an additional 0.08 m of postseismic slip on the fault. Horizontal geodetic data do not show any significant changes, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Weaver and Hill [1979] suggest that the Coso volcanics represent a local spreading center and is in an extensional state, which would allow magma to rise near the surface. Geodetic data [Savage et al, 1975] support current modest extension for the Coso region [Roquemore, 1981] in accord with the Weaver and Hill [1979] hypothesis. The presence of regional arcuate structures sparked a controversy about Coso's fundamental structural style: Austin et al [1971] and Duffield [1975] favor a calderalike structure, while Roquemore [1981] maintains that the arcuate features result from stresses induced by strike-slip faulting.…”
Section: Introductionsupporting
confidence: 51%
“…Weaver and Hill [1979] suggest that the Coso volcanics represent a local spreading center and is in an extensional state, which would allow magma to rise near the surface. Geodetic data [Savage et al, 1975] support current modest extension for the Coso region [Roquemore, 1981] in accord with the Weaver and Hill [1979] hypothesis. The presence of regional arcuate structures sparked a controversy about Coso's fundamental structural style: Austin et al [1971] and Duffield [1975] favor a calderalike structure, while Roquemore [1981] maintains that the arcuate features result from stresses induced by strike-slip faulting.…”
Section: Introductionsupporting
confidence: 51%
“…Both lines actually continue to the west from their common point in the town of Oroville, but observed and theoretically predicted displacements are small on the western extensions, so we have chosen to concentrate on those segments that will best constrain the fault slip at depth. Savage et al [1977] achieve a satisfactory fit to the displacements observed on the southern level line ( Figure 2c), but we feel that greater constraint may be placed on the extent of fault slip if both level lines are modeled simultaneously. Clark et al [1976] plot the change in elevation for the points along each of the lines between the surveys encompassing the Oroville earthquake.…”
Section: Shape Of the Slip Zone Associated With The Main Shockmentioning
confidence: 90%
“…Figure 2 compares these calculations with the observed deformation. In Figure 2c we compare the observed displacements between preearthquake and postearthquake leveling along the southern level line, corrected for the predicted subsidence due to lake loading, with predicted displacement calculated for a fault model similar to the model presented by Savage et al [1977]. In this model the fault plane runs 12 km down a 60 ø dip from its upper edge at 1.8-km depth, and it extends 10 km along its north-south strike.…”
Section: Two Level Lines Shown Inmentioning
confidence: 95%
See 2 more Smart Citations